Comparative Effect Of Rhizospheric And Endophytic Bacteria On Tcp And Caco3 Solubilization And Growth Promotion Of Wheat (triticum Aestivum L.) - Javed, S; Mazhar,M.W.; Yusof, N. Y.; Rehan, M. B. M; Hanaphi, R. M; Ahmad, N. S-H. N; Yaakob, A. S; Harun, H. C.; AZIZ, T.; Alharbi, M; Alasmari, A. F. (the Corvinus University of Budapest, 2024)
Indexed by Scopus